Successful Interprofessional Partnerships: Education and Exposure...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference February 19-21, 2015 in Cincinnati, Ohio - Miller, Brianna; Brown, Michelle; Maday, Kristopher (Clinical Laboratory Science)
There are two primary issues facing the medical laboratory today. These are the gaps in education of other healthcare professionals about what occurs in the medical laboratory and lack of exposure of the assistance that medical laboratory scientists can provide. At the University of Alabama at Birmingham, the Clinical Laboratory Sciences program has developed a relationship with the Physician Assistant program in hopes of filling these gaps. The PA program teaches a course, Clinical Laboratory Medicine, in which PA students learn about medical conditions and their relationship to laboratory results. The CLS and PA programs have partnered to allow the expertise of the CLS faculty to aid in teaching the course. This has allowed for exposure of how a MLS can be used for consultation roles when the PA is unsure of what results mean or further testing needed. Multiple CLS faulty teach in the course, while a member of the PA faculty also gives information specific to PA. This has allowed the PA students to gain an understanding of how a MLS can help them professionally, be used in a consultative role, and how laboratory tests are used in the diagnosis and treatment of patients (100% agreement, n=25). It is our hope in the future to take this same concept to other programs to develop more courses in laboratory medicine. These partnerships will aid in addressing these issues of educating other healthcare professionals about laboratory medicine and the exposure of how the MLS fits into the overall healthcare model.